2009
DOI: 10.1007/s11095-009-9869-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying of Pellets under Fasting Conditions: A Mathematical Model

Abstract: Mean gastric emptying of pellets was adequately described by the Weibull model (eta = 61.9 min, beta = 0.895), which could be applied in the design of in vitro dissolution experiments for pellet formulations with pH dependent dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…Based on visual inspection of the % remaining versus time data, three structural models were tested: namely exponential decay 34, exponential decay with a lag time 34 and a double Weibull function 35. An advantage of the latter model (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Based on visual inspection of the % remaining versus time data, three structural models were tested: namely exponential decay 34, exponential decay with a lag time 34 and a double Weibull function 35. An advantage of the latter model (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Locatelli et al . reported that the gastric emptying rate of pellets in the fasted state can be described by a Weibull function, equation (5), based on in‐vivo scintigraphic profiles [28]. The overall mean gastric emptying was estimated by fitting the mean in‐vivo scintigraphic profiles ( n = 28) to the Weibull function.…”
Section: Resultsmentioning
confidence: 99%
“…Because the gastric residence time was longer using the Weibull function than using the standard first‐order emptying constant, a total of 5 h for the passage through the upper GI tract was applied for the MR capsules in the model. PE ( t ) = 100 e ( t / 61.9 ) 0.895 where PE ( t ) is the % of pellets remaining in the stomach at a given time t (min), as described by Locatelli et al. 's Weibull fit to pellet emptying data [28]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most rate-limiting steps in the GI transit of oral dosage forms is gastric emptying (GE). The gastric residence time of a non-disintegrating, solid drug delivery system (DDS) depends on physiological factors such as the fasting or fed state of the stomach, and on the dosage form characteristics, particularly its density and size [4][5][6]. Because the residence time of a DDS in a gastric medium may affect drug release and absorption processes, the GE process has become a topic of great interest in the context of the development and optimization of a novel DDS.…”
Section: Introductionmentioning
confidence: 99%